Regional Income Inequality in Selected Large Countries - Almas Heshmati (Institute for the Study of Labor (IZA), 2004)
Income inequality can be measured at different levels of aggregation such as global, continental, international and national levels. Here we consider income inequality at the national level but the focus is on the within country regional inequality. Regional inequality in income distribution in a selection of large countries measured by the size of their population and land area with regional, provincial or federation division is examined. The empirical results reported are based on the second half of the 20th century. The countries considered here cover large transition, developing and industrialised countries. The review cover a whole range of measures and methods frequently employed in empirical analysis of income inequality and income distribution. Different determinant factors and their impacts from different studies are presented. Empirical results from the literature is compared with those obtained based on the WIID data covering post 1950.
Keywords: N30; D63; D31; I30; C10; 330; income inequality; income distribution; regions; provinces; federations; Regionale Einkommensverteilung; Regionale Disparität; Schätzung; China; Russland; Indien; Vereinigte Staaten; Kolumbien; Indonesien; Philippinen; Südafrika; Sambia; Polen